A 'marginal' region with many options: the diversity of Chalcolithic/Early Bronze Age socio-economic activities in the hinterland of Jawa. (August 2014) - Müller-Neuhof, Bernd
<x content-type="archive" xml:space="preserve">Abstract</x> In the course of the last four years, surveys in the eastern hinterland of Jawa in the Northern Badia of Jordan have revealed abundant traces of Chalcolithic/Early Bronze Age socio-economic activities. These range from the exploitation of large flint mines with associated export-oriented cortical flake production, through abundant indications of ancient pastoralism, to evidence for irrigation agriculture. Additionally, settlements inhabited all year-round have been identified far to the east of Jawa. The hypothetical link of these activities with the site of Jawa is discussed and the possible affiliation of this desert culture to a supra-regional desert culture connecting the Northern Badia in Jordan with the Sinai is considered.